A Decade of Viral Evolution (2015–2025): Emergence, Mutations, and Implications for Global Health - Satish Kumar Sarankar (International Journal of Vaccines, 2025)
Over the past decade (2015-2025), viral evolution has profoundly reshaped the global health landscape, challenging healthcare systems, diagnostic tools, therapeutic strategies, and vaccine efficacy. This review comprehensively analyzes the evolutionary trajectories of major human and zoonotic viruses, with a focus on pandemic-prone, drug-resistant, and emerging pathogens. Viral evolution is driven by diverse molecular mechanisms including high mutation rates, recombination, reassortment, host immune pressure, and antiviral interventions, leading to genetic diversification, immune escape, cross-species transmission, and resistance development. SARS-CoV-2 serves as a prime example of real-time viral evolution, with its transition from early variants (Alpha, Beta, Gamma, Delta) to the highly immune-evasive Omicron sublineages (BA.1–BA.5, XBB, JN.1), each shaped by mutations in the spike protein influencing transmissibility and vaccine escape. Influenza A virus continues its seasonal drift and reassortment, notably in H5N1 clade 2.3.4.4b, emphasizing the challenges in surveillance and vaccine matching. Meanwhile, viruses such as Lloviu, Oropouche, and West Nile are expanding their geographic and host range, often unnoticed due to surveillance gaps. Drug-resistant strains of Hepatitis B, HIV-1, and Enterovirus D68 highlight the urgent need for continuous genomic monitoring and therapeutic innovation. Chronic infections foster quasispecies evolution, promoting persistence and treatment failure. Zoonotic spillovers and climate-driven mutations further compound the risks of future outbreaks. This review underscores the necessity of a multidisciplinary “One Health” approach integrating human, animal, and environmental health surveillance. Future directions include leveraging artificial intelligence for predictive viral genomics, developing pan-viral and universal vaccine platforms (e.g., mRNA, nanoparticle-based), and investing in genomic surveillance infrastructure globally. Understanding the decade-long evolution of viruses is critical for preemptive action, vaccine design, public health preparedness, and developing robust antiviral strategies. The insights offered here aim to inform future policies and research directions in an era marked by dynamic viral threats.
Keywords: AI in viral outbreak prediction; Challenges in developing universal vaccines; Emerging viruses; Global health threats; Impact of virus mutations on vaccines; Influenza virus evolution; One Health approach; SARS-CoV-2 variants; Vaccine adaptation strategies; Virus mutations; Zoonotic spillover